Interactive 3D Simulator for Autostereoscopic Display Systems - Park, Min-Chul; Lee, Ho-Dong; Son, Jung-Young (IDW'11: PROCEEDINGS OF THE 18TH INTERNATIONAL DISPLAY WORKSHOPS, VOLS 1-3, 2011)
Crosstalk to reduce leakage of one eye's image into the image of the other eye, and light intensity for computing visual comfort zone are important factors in designing autostereoscopic display system. Interaction enables instinctive design. This paper describes an interactive 3D simulator to design the system instinctively in 3D space.